Answer:
[tex]\large\boxed{3.\ y-(-7)=-2(x-2)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
Let [tex]k:y=m_1x+b_1,\ l:y=m_2x_b_2[/tex].
[tex]l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\if m_1=m_2[/tex]
================================================
We have the equation of the line:
[tex]y=\dfrac{1}{2}x-5\to m_1=\dfrac{1}{2}[/tex]
Therefore
[tex]m_2=-\dfrac{1}{\frac{1}{2}}=-2[/tex]
Put it and coorinates of the point (2, -7) to the equation of a line
in the point-slope form:
[tex]y-(-7)=-2(x-2)\\\\y+7=-2(x-2)[/tex]